2016
DOI: 10.1016/j.cryobiol.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of human spermatozoa with minimal non-permeable cryoprotectant

Abstract: Cryopreservation of human spermatozoa is a commonly used technique in assisted reproduction, however freezing low concentrations of sperm while maintaining adequate post-thaw motility remains a challenge. In an effort to optimize post-thaw motility yields, low volumes of human sperm were frozen in polyimide-coated fused silica micro-capillaries using 0.065 M, 0.125 M, 0.25 M, or 0.5 M trehalose as the only cryoprotectant. Micro-capillaries were either initially incubated in liquid nitrogen vapor before plungin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 29 publications
1
25
1
Order By: Relevance
“…This demonstrated that the osmolarity in the cryopreservation medium is of importance to sperm parameters. Higher concentrations of trehalose, over 50 mM, may cause the osmolarity to become too high, and can produce substantial osmotic damage, and again this is consistent with another, previous study 3,12 ; whereas the osmolarity has a significant effect on human sperm motility. Gao et al 14 suggested that appropriate osmolarity of the cryopreservation medium is between 250 and 350 milliosmoles per liter.…”
Section: Figuresupporting
confidence: 89%
See 2 more Smart Citations
“…This demonstrated that the osmolarity in the cryopreservation medium is of importance to sperm parameters. Higher concentrations of trehalose, over 50 mM, may cause the osmolarity to become too high, and can produce substantial osmotic damage, and again this is consistent with another, previous study 3,12 ; whereas the osmolarity has a significant effect on human sperm motility. Gao et al 14 suggested that appropriate osmolarity of the cryopreservation medium is between 250 and 350 milliosmoles per liter.…”
Section: Figuresupporting
confidence: 89%
“…Although animal studies showed the benefits of trehalose over sucrose in sperm freezing, only a few studies have investigated the effects of trehalose on human sperm cryopreservation. 3,12 Cryopreservation adversely affected the cryosurvival of human spermatozoa. Unsurprisingly, in our study, progressive motility, total motility, vitality and morphology of spermatozoa; after the frozen-thawed process, was significantly reduced when compared with the fresh semen values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Raman images obtained suggest that the higher post‐thaw recovery for cells cryopreserved in SGC results from the ability of the molecule to penetrate the cell membrane (Figure ). The importance of penetrating cryoprotectants on post‐thaw recovery has long been known (Mazur, ), but a recent study has found that nonpenetrating cryoprotectants can also provide protection (Liu et al, ). In addition, cell types may respond differently to the same formulation.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The freezing and thawing of sperm cells of three patients with distinct seminal characteristics (i.e., normozoospermia, oligozoospermia and asthenozoospermia) is much more successful on the icephobic soot compared to an uncoated glass substrate and about 80% of initial sperm motility is recovered [157]. Such an outcome is very unexpected and emotive, because a recent study reports not more than 70% recovered motility achieved through larger quantity of cryoprotectants in the seminal suspension [160]. Of course, notwithstanding of the positive feedback from the scientific community ("highly innovative and unconventional approach"; "an eye-opening short communication", etc.…”
Section: Fundamentally New Potential Applications Of the Passive Icepmentioning
confidence: 95%